Kewenangan Pemerintah Daerah Di Bidang Pertanahan - Dady Hendrawan; Hendrich Juk Abeth; Ayu Syaputri (LPPM STIH Awang Long, 2018)
In Article 33 paragraph 3 of the 1945 Constitution of the Republic of Indonesia it is stated that;